1997
DOI: 10.1097/00005373-199712000-00013
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Association of Helicopter and Ground Ambulance Transport with the Outcome of Injury in Trauma Patients Transported from the Scene

Abstract: The large majority of trauma patients transported by both helicopter and ground ambulance have low injury severity measures. Outcomes were not uniformly better among patients transported by helicopter. Only a very small subset of patients transported by helicopter appear to have any chance of improved survival based on their helicopter transport. This study suggests that further effort should be expended to try to better identify patients who may benefit from this expensive and risky mode of transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(86 citation statements)
references
References 30 publications
3
79
0
4
Order By: Relevance
“…Cunningham and colleagues published a study showing no significant benefit of AMT and suggested that this mode of transport was overused in patients with minor injuries. 14 In their study, however, a large proportion of the patients transported had an ISS < 12 and likely did not warrant HEMS. They did, however, stratify their results and showed a significant benefit of AMT in patients with an ISS between 21 and 30.…”
Section: Discussionmentioning
confidence: 87%
“…Cunningham and colleagues published a study showing no significant benefit of AMT and suggested that this mode of transport was overused in patients with minor injuries. 14 In their study, however, a large proportion of the patients transported had an ISS < 12 and likely did not warrant HEMS. They did, however, stratify their results and showed a significant benefit of AMT in patients with an ISS between 21 and 30.…”
Section: Discussionmentioning
confidence: 87%
“…35 Many studies have shown no such improvement. 26,[36][37][38][39][40] Given the relative lack of clear evidence for the benefit in terms of outcome, and in view of the high costs and the issue of safety, HEMS systems are under increasing scrutiny. 9,12 This is one of the few large studies to evaluate the association between EMS transportation mode and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Other published studies have disputed the ''shorter is better'' philosophy. 5,6,[27][28][29] Several of these studies had findings that were the result of a secondary analysis, while others had obvious selection bias, or looked only at patients with extremely long total out-of-hospital times.…”
Section: 19mentioning
confidence: 99%
“…[4][5][6] One of these referenced articles by Cowley refers to an article by Foster that says the mortality rate triples for every 30-minute increase from time of injury to definitive care. 7 This 1969 article by Foster reviews the state of helicopter transport at the time and discusses disagreement among physicians as to whether time is an important factor in trauma care.…”
mentioning
confidence: 99%